2020
DOI: 10.31083/j.rcm.2020.03.60
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of medical management versus catheter ablation for atrial fibrillation

Abstract: Several observational studies have shown a survival benefit for patients with atrial fibrillation (AF) who are treated with catheter ablation (CA) rather than medical management (MM). However, data from randomized controlled trials (RCTs) are uncertain. Therefore, we performed a meta-analysis of RCTs that compared the benefits of CA and MM in treatment of AF. We searched the Cochrane Library, PubMed, and EMBASE databases for RCTs that compared AF ablation with MM from the time of database establishment up to J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Additionally, Mao et al 25 18 reported no statistically significant difference in procedure success rates after cryoablation between patients with paroxysmal AF and persistent AF (52% vs. 41%, p = .36).…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, Mao et al 25 18 reported no statistically significant difference in procedure success rates after cryoablation between patients with paroxysmal AF and persistent AF (52% vs. 41%, p = .36).…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 96%
“…However, all studies included in the AlTurki review were randomized controlled trials, different from our approach, and used mainly single-arm studies. Mao et al 25 supported using CA to reduce mortality.…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 99%
“…Catheter ablation, surgical ablation, and hybrid therapy have all been proposed as treatments for AF, but they vary in efficacy and accessibility. In recent years, transvenous catheter ablation of pulmonary vein isolation (PVI) has been the treatment of choice for symptomatic patients who require rhythm control and fail antiarrhythmic drug therapy (30)(31)(32)(33).…”
Section: Catheter and Surgical Ablationmentioning
confidence: 99%
“…However, there is still recurrence or thromboembolic events (TEs) in patients with AF after CA. 6 Thromboembolic complications are the main cause of death and disability in AF. 7 Although anticoagulant therapy reduces the incidence of thromboembolism, 8 it also has its limitations.…”
Section: Introductionmentioning
confidence: 99%